Life Cycle Assessment And Performances of Revived Industrial Lead-Acid Batteries Through Regeneration Technology : Regeneration Technology - Ponniran , Asmarashid; Sahruddin , Nursyaheera (Evolution in Electrical and Electronic Engineering, 2020)
The growing amount of battery production will produce more substances which increase the number of harmful chemicals to the environment such as carbon dioxide, nitrogen, and sulfur dioxide. Since most Malaysians are thrown their old batteries away and replace with new batteries. The recycled batteries and revived batteries are ways to reduce the number of batteries being disposed of. Hence this study aims to determine the carbon footprint and performances of revived industrial lead-acid batteries through regeneration technology. In this study, life cycle assessment is used as a method to assess environmental impacts on which carbon footprint associated with all the stages of a batteries’ life through the regeneration technology. The three processes involved in regeneration technology which charging process, discharging process, and regeneration process to evaluated the voltage, capacity, and specific gravity. From the results, the revived industrial lead-acid batteries through regeneration technology are 199.91 kgCO2-eq of a carbon footprint than recycled batteries and the discharge time of 6 batteries are increased from 3 hours 55 minutes to 5 hours after using the regeneration technology. Thus, it is confirmed the revived industrial lead-acid batteries through regeneration technology are to be used preferably in reducing the disposed of batteries.